A comparison study of NoSQL document-oriented database system - Suma, Sugimiyanto; Alqurashi, Fahad (International Journal of Applied Mathematical Research, 2019)
By increasing data generation at these day, requirement for a sufficient storage system are strongly needed by stakeholders to store and access huge number of data in efficient way for fast analysis and decision. While RDBMS cannot deal with this challenge, NoSQL has emerged as a solution to address this challenge. There have been plenty of NoSQL database engine with their categories and characteristics, especially for document-oriented database. However, it makes a confusion for the system developer to choose the appropriate NoSQL database for their system. This paper is our preliminary report to provide a comparison of NoSQL databases. The comparison is based on performance of execution time which is measured by building a simple program. This experiment was done in our local cluster by exploiting around 1 million datasets. The result shows that RDB has better performance than CDB in terms of execution time.